2019
DOI: 10.1002/ijgo.12752
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30‐day morbidity after hysterectomy for benign disease

Abstract: Objective To determine the 30‐day morbidity rate after hysterectomy for benign disease and identify predictors of 30‐day morbidity. Methods A retrospective study was conducted among women undergoing hysterectomy for benign indications between January 1, 2010, and December 31, 2015, at Konkuk University Hospital, South Korea. Multivariable regression analysis identified independent factors for morbidity. Results 1609 women were included. 30‐day morbidity rates were 4.5% (n=72) for the whole cohort: 7.5% (28/371… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Mereu et al reported a mean age of 49.6 ± 6.5 years among patients who underwent TLH due to benign diseases [10]. Shim et al also reported a mean age of 48 years [11].…”
Section: Discussionmentioning
confidence: 99%
“…Mereu et al reported a mean age of 49.6 ± 6.5 years among patients who underwent TLH due to benign diseases [10]. Shim et al also reported a mean age of 48 years [11].…”
Section: Discussionmentioning
confidence: 99%
“…Determination of pre-operative comorbid medical conditions, ensuring pre-operative optimization of them and the appropriate selection of surgical approaches are important; however, this may not always be possible in emergency surgeries. In the 5-year retrospective study of Shim et al,[ 26 ] the 30-day morbidity rate was determined to be 4.5% (n=72) in patients (n=1609) undergoing hysterectomy for benign indications. Urinary complications wound infection, blood transfusion more than 4 units, and Charlson comorbidity index of 2 or more, OT were determined to be independent risk factors for morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint was 30‐day postoperative morbidity according to the National Surgical Quality Improvement Program 21 . The postoperative variables for comparing surgical outcomes between the two groups were as follows 22–25 : time to surgery; estimated blood loss (EBL); hemoglobin change; time to resume a normal diet; length of postoperative hospital stay; conversion to laparotomy; and 30‐day readmission after hysterectomy. The operative time was defined as the time from skin incision to skin closure.…”
Section: Methodsmentioning
confidence: 99%